Nutritional and environmental co-benefits of shifting to "Planetary Health" Spanish tapas. (20th October 2020) - Batlle-Bayer, Laura; Bala, Alba; Roca, Mercè; Lemaire, Elodie; Aldaco, Rubén; Fullana-i-Palmer, Pere
Abstract: While strong focus has been recently given to the environmental burdens of diets, more research is needed at the daily eating patterns, specifically, at the meal level. In this regard, this study attempts to enlarge this knowledge by evaluating the environmental performance of meals eaten away from home. In particular, this paper focuses on the case of shared dishes, known as tapas, eaten in a Spanish restaurant. To do so, the life cycle assessments (LCA) of 15 tapas meals are performed, and a functional unit based on the caloric energy intake and the nutritional quality of the meals is applied. This novelty, at the meal level, allows the integration of both environmental and the nutritional aspects, and, therefore, the comparison between meals differing in energy and nutrient content. Additionally, to better assess and compare the performance of the meals, this study estimates the benchmarks for the three evaluated environmental impacts - Global Warming Potential (GWP), Blue Water Footprint (BWF) and Land Use (LU) – based on the Planetary Health Diet. The results suggest that shifting towards a planetary health tapas meal, a more plant-based one, can significantly reduce GWP, BWF and LU. The restaurant stage, followed by the primary production, largely contributes to GWP, and food losses and waste (FLW) plays an important role, contributing significantly to all three impacts. Strategies towards energy efficiency at the restaurant, innovation in the menus, and reducing FLW are required, as well as further engagement between the HORECA sector and the academia to work in line towards sustainable eating patterns. Graphical abstract: Image 1 Highlights: An energy- and nutrient-based FU is used to assess the LCA of tapas meals. Meals can only be environmentally compared if they have the same nutritional function. Primary production and the restaurant stages contribute the most to GWP. Large environmental benefits when shifting to a more plant-based tapas meal. Reducing food losses and waste can bring large environmental benefits.